2021
DOI: 10.1108/jbsed-02-2021-0017
|View full text |Cite
|
Sign up to set email alerts
|

The influence of non-governmental organizations (NGOs) on the development of voluntary sustainability accounting reporting rules

Abstract: PurposeThe purpose of this paper is to show the impact that non-governmental organizations (NGOs) have on the evolution of Global Reporting Initiative (GRI). GRI is a sustainability report disclosed by business organizations to meet the demands and interests of various stakeholders. These stakeholders’ needs have influenced GRI and its guidelines.Design/methodology/approachThe methodology for this paper is library-based archival research. It is qualitatively and analytically descriptive of prior academic resea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 35 publications
1
58
0
1
Order By: Relevance
“…Accordingly, the study of Höck et al ( 2020 ) investigated the effect of sustainability in environmental aspects on the costing of credit risk for European institutions, and they analyzed if the credit eligibility of an institution has a moderating impact on the relationship between the sustainability in environmental aspects and the premium of credit risk, the study found that lower credit risk premiums will be resulted by more sustainable institution if they also have a high credit eligibility. On the other side, the study of Sisaye ( 2021 ) found that the diffusion of institutions’ sustainability is worldwide, but differences exist among countries; institutions have a board of directors that is elected and/or appointed from both outside and inside the organization, while there are variations in the relative impact of board among countries; they all are in charge for institutions’ sustainability.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Accordingly, the study of Höck et al ( 2020 ) investigated the effect of sustainability in environmental aspects on the costing of credit risk for European institutions, and they analyzed if the credit eligibility of an institution has a moderating impact on the relationship between the sustainability in environmental aspects and the premium of credit risk, the study found that lower credit risk premiums will be resulted by more sustainable institution if they also have a high credit eligibility. On the other side, the study of Sisaye ( 2021 ) found that the diffusion of institutions’ sustainability is worldwide, but differences exist among countries; institutions have a board of directors that is elected and/or appointed from both outside and inside the organization, while there are variations in the relative impact of board among countries; they all are in charge for institutions’ sustainability.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Civil society actors, NGOs and interest groups have been found to be key stakeholders in a range of sustainability issues, including gender diversity, and can shape firm practices in the long term (Sisaye, 2021).…”
Section: Methodsmentioning
confidence: 99%
“…Both formal and informal institutions interact at different levels, producing outcomes that have significant implications for increasing "productive" entrepreneurial activity (Aparicio, Turro, and Noguera 2020;Baumol 1990;North 1990). Therefore, the institutional theory could be useful for understanding which institutional variables encourage entrepreneurial activity that contributes to economic growth in emerging economies (Bjørnskov and Foss 2013;Bruton, Ahlstrom, and Li 2010;Sisaye 2021;Veciana and Urbano 2008;Hasan and Hassan 2021).…”
Section: The Importance Of Entrepreneurship Institutions and Economic Growthmentioning
confidence: 99%